Christianity and change in Northeast India - Subba, Tanka Bahadur; Puthenpurakal, Joseph; Puykunnel, Shaji Joseph (New Delhi : Concept Pub. Co., 2009)
Contributed seminar papers.
Includes bibliographical references and index.
Keywords: Christianity and culture -- India, Northeastern -- Congresses; Christianity -- India, Northeastern -- Influence -- Congresses; Tribes -- India, Northeastern -- Social life and customs -- Congresses; Women in church work -- India, Northeastern -- Congresses